RESEARCH OF TEMPERATURE DISTRIBUTION IN THE PROCESS OF THERMO-FRICTIONAL CUTTING OF TITANIUM ALLOY TI-5553 - Sherov, Karibek; Ainabekova , Saule; Kuanov, Issa; Myrzakhmet, Balgali; Bekzhanov, Yeldos; Gabdyssalik, Riza; Mazdubay, Assylkhan; Kamarov, Aman; Sherov, Aibek (Journal of Applied Engineering Science, 2022)
This article presents the results of studying the temperature distribution in the process of thermo-frictional cutting of titanium alloy Ti-5553. The process was simulated using the Machining module of the DEFORM 3D software package based on the finite element method. It was found that when cutting off the titanium alloy Ti-5553, depending on the geometry of the circular saw, the temperature in the "disk-workpiece" contact zone reached T = 800 ÷ 1130 °C, and its propagation into the depth of the workpiece was 0.66 ÷ 0.96 mm. The optimal geometry of a circular saw for cutting off titanium alloy Ti-5553: L1 = 18 mm, L2 = 14 mm, в = 2 mm.The research was carried out within the framework of the grant № AP09562459.
Keywords: thermal cutting, pulse cooling, temperature, heating zone, cooling zone, circular saw